2022
DOI: 10.1002/ange.202206399
|View full text |Cite
|
Sign up to set email alerts
|

Heterogenised Molecular Catalysts for Sustainable Electrochemical CO2 Reduction

Abstract: There has been a rapid rise in interest regarding the advantages of support materials to protect and immobilise molecular catalysts for the carbon dioxide reduction reaction (CO2RR) in order to overcome the weaknesses of many well‐known catalysts in terms of their stability and selectivity. In this Review, the state of the art of different catalyst‐support systems for the CO2RR is discussed with the intention of leading towards standard benchmarking for comparison of such systems across the most relevant suppo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 109 publications
0
2
0
Order By: Relevance
“…9,10 On the other hand, homogeneous metal complexes are essential systems for studying CO 2 RR mechanisms at a molecular level, offering superior selectivity and exceptional activity. [11][12][13] Wang and co-workers found that homogeneous catalysts were actually dynamically adsorbed on the electrode surface in a homogeneous system. 14 These metal complexes allow for precise tailoring of well-defined active site structures.…”
Section: Introductionmentioning
confidence: 99%
“…9,10 On the other hand, homogeneous metal complexes are essential systems for studying CO 2 RR mechanisms at a molecular level, offering superior selectivity and exceptional activity. [11][12][13] Wang and co-workers found that homogeneous catalysts were actually dynamically adsorbed on the electrode surface in a homogeneous system. 14 These metal complexes allow for precise tailoring of well-defined active site structures.…”
Section: Introductionmentioning
confidence: 99%
“…However, these shortcomings can be mitigated via heterogenisation of the molecular complexes on solid supports, [12][13][14][15] which bridges between homogenous and heterogeneous systems and provides an opportunity to precisely regulate the structure of the active site on solid support at atomic levels. The primary coordination environment around the central metal active site plays a crucial role controlling the catalytic reaction.…”
Section: Introductionmentioning
confidence: 99%